The Management of Global Careers Exploring the Rise of International Work (Springer International Publishing, 2018)
'This book is an invaluable resource for scholars in the field of global careers, for people experiencing or contemplating such a career, and for those who manage them. The team of experts assembled provides a wonderful breadth of perspectives and a rich coverage of the field.' -Hugh P. Gunz, Professor, University of Toronto Mississauga 'A rich collection of knowledge about diverse types, experiences, and issues of global careerists... an indispensable resource for global career researchers, educators, and practitioners.' -Margaret Shaffer, Michael F. Price Chair of International Business, University of Oklahoma Exploring global career issues in-depth, this important collection works at the intersection of career management and international HRM. It uses a multitude of perspectives to explore global career drivers, experiences and outcomes for individuals, as well as career systems and management within organisations and societies. Both long-term and short-term careers are discussed and examined alongside the impact that they have on elements of family life, providing a useful guide for academic scholars, HR managers and professionals operating in global environments.